Patients with Invasive Tumors and eNOS Gene Polymorphisms with Subarachnoid Hemorrhage Tend to Have Poorer Prognosis - Siroya, Hardik Lalit; Devi, Bhagavatula Indira; Aripirala, Prasanthi; Ramesh, Shruthi Shimoga; Bhat, Dhananjaya Ishwar; Shukla, Dhaval Prem; Konar, Subhash Kanti; Christopher, Rita (Asian Journal of Neurosurgery, 2022)
Context Endothelial nitric oxide synthase (eNOS) gene polymorphisms are found to predict predisposition to aneurysmal rupture and development of vasospasm in a patient of subarachnoid hemorrhage (SAH). eNOS gene polymorphisms are also found to predict invasiveness of malignant cells. Studies are not available in literature to describe the effect of eNOS gene polymorphisms and correlation between aneurysm and carcinoma. This study aims to investigate whether positive cancer history influences clinical outcome following SAH and eNOS gene polymorphisms.Materials and Methods The eNOS gene polymorphisms were analyzed in seven consecutive patients (mean age, 52.28 ± 20 years) with a diagnosis of invasive systemic tumors from 2011 to 2017. The eNOS 4a/4b eNOS -786T> eNOS894G > T polymorphisms of the eNOS gene were determined by polymerase chain reaction and restriction fragment length polymorphism.Results Seven patients of aneurysmal SAH in association with malignancies were studied for eNOS polymorphisms expression and outcome. Three patients had carcinoma cervix: one patient of carcinoma breast and one each of transitional cell carcinoma of urinary bladder, spindle cell carcinoma of left kidney, and untreated patient of atypical pituitary (adenoma). A genotype study of eNOS gene polymorphisms in these patients shows common polymorphisms are involved in the determination of disease progression in malignancies and aneurysmal SAH.Conclusion Patients who expressed 4ab, eNOS -786T > TT/CC/TC, eNOS894G > T GG/GT polymorphisms did better than patients who expressed only 4bb, though both were associated with poor prognosis.
Keywords: invasive malignancy/tumors; eNOS gene polymorphisms; intracranial aneurysms